BISNIS HARAM DAN PENGARUHNYA TERHADAP FISIK DAN PSIKIS MANUSIA - Zumaroh Zumaroh (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2017)
Abstract: One form of work someone does to produce a variety of products is business. For Muslims, business is always controlled by the law of halal and haram, both in the way of acquisition and utilization. Physically, a person’s malicious practices will result in enormous losses, he will experience various diseases that are difficult to cure or even no cure. This affects the depletion of the treasures it has collected in such haram ways. Psychically, the warning and punishment sanctions experienced by malbic businessmen are more dire. In addition to causing various traits and bad traits within himself and his family, he will also experience severe depression and shudder as a manifestation of the aridity of the soul due to his evil behavior in business.